Give me some truth : a novel with paintings - Gansworth, Eric., 1965- (Arthur A. Levine Books, an imprint of Scholastic Inc., 2018)
In 1980 life is hard on the Tuscarora Reservation in upstate New York, and most of the teenagers feel like they are going nowhere: Carson Mastick dreams of forming a rock band, and Maggi Bokoni longs to create her own conceptual artwork instead of the traditional beadwork that her family sells to tourists--but tensions are rising between the reservation and the surrounding communities, and somehow in the confusion of politics and growing up Carson and Maggi have to make a place for themselves.